Antibiotic Prophylaxis With Cefuroxime: Influence of Duration on Infection Rate With Staphylococcus aureus in a Contaminated Open Fracture Model. Issue 4 (April 2018) - Puetzler, Jan; Metsemakers, Willem-Jan; Arens, Daniel; Zeiter, Stephan; Kuehl, Richard; Raschke, Michael J.; Richards, Robert Geoff; Moriarty, Thomas Fintan
Abstract : Objectives: The optimal duration of perioperative antibiotic prophylaxis (PAP) for open fractures remains controversial because of heterogeneous or unclear guidelines and highly variable prophylactic regimens in clinical practice. We aimed at testing different PAP durations under controlled conditions in a contaminated rabbit fracture model. Methods: A complete humeral osteotomy in 18 rabbits was fixed with a 7-hole locking compression plate and inoculated with Staphylococcus aureus. Cefuroxime was administered in a weight-adjusted dosage equivalent to human medicine (18.75 mg/kg). PAP was administered as a single shot only; for 24 hours; or for 72 hours in separate groups of rabbits (n = 6 per group). Infection was assessed after 2 weeks by quantitative bacteriological evaluation of the tissues and hardware. Results: Postoperative duration of PAP had a significant impact on the success of antibiotic prophylaxis in this model. Whereas the single-shot regimen completely failed to prevent infection, the 24-hour regimen showed a reduced infection rate (1 of 6 rabbits infected), but only the 72-hour course was able to prevent fracture-related infection in all animals in our model. Conclusions: When contamination with high bacterial loads is likely (eg, in an open fracture situation), a 72-hour course of intravenous cefuroxime seems to be superior in preventing fracture-related infection in our rabbit model compared with a single-shot or 24-hour antibiotic regimen. Abstract : Supplemental Digital Content is Available in the Text.